Pupil dilation dynamics with an intracameral fixed combination of mydriatics and anesthetic during cataract surgery. Issue 3 (March 2018) - Chiambaretta, Frederic; Pleyer, Uwe; Behndig, Anders; Pisella, Pierre‐Jean; Mertens, Erik; Limao, Antonio; Fasce, Francesco; Fernandez, Joaquin; Benmoussa, Salah‐Eddine; Labetoulle, Marc; Cochener, Beatrice; Hartani, Dahbia; et al.
Abstract : Purpose: : To compare the pupil dynamics of an intracameral combination of 2 mydriatics and 1 anesthetic (Mydrane) to a standard topical regimen for cataract surgery. Setting: : Sixty‐two centers in Europe and 6 centers in Algeria. Design: : Prospective case series. Methods: : Pupil size measurements were performed in 2 randomized studies (phase 2 and phase 3) under masked conditions (recorded videography, masked reading center). The outcomes in the phase 2 study supported evaluation of the timeframe to obtain pupil dilation and the phase 3 study provided results on mydriasis stability. Results: : Phase 2 and phase 3 comprised 139 patients and 591 patients, respectively. After intracameral combination administration, 95% of the pupil dilation was achieved within a mean of 28.6 seconds ± 4.6 (SD). At the beginning of capsulorhexis creation, the mean pupil diameter was larger than 7.0 mm in both groups. The intraoperative pupil diameter remained stable in the intracameral combination group and decreased in the topical group. The mean change in pupil size just before capsulorhexis to the end of surgery (just before cefuroxime injection) was −0.22 ± 0.72 mm and −1.67 ± 0.98 mm, respectively. No clinically significant change in pupil diameter (change <1.0 mm) occurred in the majority of the intracameral combination group (89.3%) compared with the topical group (26.8%). Conclusions: : Intracameral combination of 2 mydriatics and 1 anesthetic is an alternative to topical mydriatics for cataract surgery. The prompt onset of pupil dilation and the stable mydriasis induced by this drug combination improved the intraoperative conditions during crucial steps, such as intraocular lens implantation.